The Influence Of Coloring Play Therapy On Anxiety Levels Of Preschool-Age Children Who Are Hospitalized In Aceh Mother And Child Hospital - Desrina Desrina; Yadi Putra; Maria Ulfa (International Journal of Medicine and Health, 2023)
Anxiety is the most common feeling experienced by pediatric patients who experience hospitalization, anxiety that is often felt by children such as crying, fear of the environment and new people. The number of stressors experienced by children when undergoing hospitalization can have a negative impact on the child's development. This aim is to determine the effect of coloring play therapy on the anxiety level of preschool-aged children who experience hospitalization at the Banda Aceh Mother and Child Hospital. This study used a quantitative research design with a sample size approach of 5 respondents. The sampling technique used is purposive sampling. Data collection instruments were carried out before and after carrying out coloring play therapy using observation sheets with a percentage calculation assessment scale. The results showed that before being given coloring play therapy, there were 2 respondents who experienced moderate anxiety (40%) and 3 child respondents who experienced severe anxiety (60%). And after being given coloring play therapy there were 4 child respondents who experienced mild anxiety (80%) and 1 person who was in the moderate category (20%). It is suggested that the results of this study can be used as a reference for coloring play therapy in preschool-age child patients who experience hospitalization anxiety in the children's room at the Banda Aceh mother and child hospital in 2021.